Sustaining Engagement in Duolingo: Autonomy and the Dynamic Nature of Situational Motivation in Self-Directed Language Learning - Anggi Purwa Lestarina; Lambok Hermanto Sihombing; Puji Lestari (Universitas Islam Negeri Palopo, 2026)
Mobile-assisted language learning (MALL) offers flexible opportunities for self-directed language learning (SDL), yet how learners sustain engagement outside formal classrooms remains insufficiently understood, especially when motivation interacts with self-regulation and context. This study examined barriers experienced by Indonesian university students using Duolingo and explored how situational motivation related to fluctuations in engagement. A qualitative descriptive case study involved ten university students; the small sample supported in-depth analysis but limited transferability. Data were collected through an open-ended survey and semi-structured interviews and were analyzed thematically using Garrison’s (1997) SDL framework. Internal barriers included mood fluctuation, stress and fatigue, time-management difficulties, and limited self-monitoring. External barriers included repetitive or insufficiently challenging materials, dependence on assigned targets, environmental distractions, limited family awareness, and peer influence. Situational motivation emerged as salient because engagement shifted in response to immediate cues, including assignments, deadlines, targets, and peer reminders, rather than remaining stable across situations. The findings add contextual nuance to Garrison’s framework by showing that mobile-assisted SDL is shaped by interactions among learner readiness, task design, and social context. Educators and app designers should use structured goals, adaptive challenge, reflection, and social support to sustain engagement. These supports may gradually strengthen independent regulation beyond externally prompted participation.